2023
DOI: 10.3390/antiox12101882
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae as a Sustainable Source of Antioxidants in Animal Nutrition, Health and Livestock Development

Alexandros Mavrommatis,
Eleni Tsiplakou,
Anastasia Zerva
et al.

Abstract: Microalgae are a renewable and sustainable source of bioactive compounds, such as essential amino acids, polyunsaturated fatty acids, and antioxidant compounds, that have been documented to have beneficial effects on nutrition and health. Among these natural products, the demand for natural antioxidants, as an alternative to synthetic antioxidants, has increased. The antioxidant activity of microalgae significantly varies between species and depends on growth conditions. In the last decade, microalgae have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 170 publications
1
2
0
Order By: Relevance
“…SOD and CAT are pivotal antioxidant enzymes in microalgal cells, with SOD acting as the first defense against oxidative stress. Moreover, carotenoids have antioxidant characteristics and maintain cells against free radicals, inhibit lipid peroxidation, increase the stability of the photosynthetic apparatus, and protect integrity membranes [86]. In this study, 10 −6 M IAA, GA3, and ZT significantly increased the levels of antioxidant enzymes SOD and CAT as well as carotenoids (Figure 3B), indicating that O. borgei enhanced antioxidant capacity in response to abiotic stress.…”
Section: Mitigation Of Oxidative Stress Damage Caused By Abiotic Stre...supporting
confidence: 51%
“…SOD and CAT are pivotal antioxidant enzymes in microalgal cells, with SOD acting as the first defense against oxidative stress. Moreover, carotenoids have antioxidant characteristics and maintain cells against free radicals, inhibit lipid peroxidation, increase the stability of the photosynthetic apparatus, and protect integrity membranes [86]. In this study, 10 −6 M IAA, GA3, and ZT significantly increased the levels of antioxidant enzymes SOD and CAT as well as carotenoids (Figure 3B), indicating that O. borgei enhanced antioxidant capacity in response to abiotic stress.…”
Section: Mitigation Of Oxidative Stress Damage Caused By Abiotic Stre...supporting
confidence: 51%
“…The inclusion of microalgae in animal diets has gained widespread attention for aquaculture, as well as the production of poultry, monogastric mammals, and ruminants (El-Ghany 2020 ; Ma et al 2024 ; Madeira et al 2017 ; Martins et al 2021 ). Microalgae are abundant in aquatic environments, possessing favorable characteristics such as rapid proliferation, widespread habtitats, and environmental adaptability, which make them easily accessible as natural food and feed sources for various aquatic organisms (Olabi et al 2023 ; Udayan et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae are of high commercial value and also produce proteins, lipids, vitamins, pigments, cosmetics, and food and feed additives [4]. Microalgae offer a renewable and sustainable way to obtain bioactive substances like essential amino acids, polyunsaturated fatty acids, and antioxidants, which have been documented to have beneficial effects on health and nutrition [5]. Prior studies have confirmed the effectiveness of microalgae in serving as a source of fucoxanthin, with diatoms exhibiting a goldenbrown hue, attributed to their richness in pigments such as fucoxanthin [6,7].…”
Section: Introductionmentioning
confidence: 99%